Environmental protection in China land-use management - Bennett, Jeff, 1954-; Wang, Xuehong, 1970-; Zhang, Lei.; Edward Elgar Publishing (Cheltenham [England] ; Northampton, Mass. : Edward Elgar, 2008)
Faced with intensified environmental degradation and decreased agricultural land productivity, the Chinese government has sought policy interventions to reverse both of these negative trends. Among the policy instruments is the Conversion of Cropland to Forest and Grassland Program (CCFGP) that aims to change the pattern of agricultural land use in 25 provinces and autonomous regions across China. This book provides the most comprehensive assessment of the CCFGP undertaken to date. It allows the consideration of fundamental questions pertaining to the sustainability of the land use changes brought about by the CCFGP, its cost effectiveness and the prospects for policy evolution. Contributions from a wide range of economists and scientists in the book provide policymakers in the Chinese government with relevant information with which to pursue more effectively agro-environmental goals.
1. Agriculture and the environment / Jeff Bennett -- 2. Land-use management in China / Xuehong Wang, Hongyun Han and Jeff Bennett -- 3. The Conversion of Cropland to Forest and Grassland Program / Jeff Bennett ... [et al.] -- 4. Are farmers better off? / Chen Xie ... [et al.] -- 5. Economic efficiency impacts / Jeff Bennett ... [et al.] -- 6. Valuing run-off reductions / Jeff Bennett ... [et al.] -- 7. Non-market values of environmental changes / Xuehong Wang ... [et al.] -- 8. An overall assessment of the CCFGP and policy recommendations / Xuehong Wang ... [et al.] -- 9. The way ahead / Jeff Bennett and Xuehong Wang.
Includes bibliographical references and index.
Keywords: Land use, Rural -- Government policy -- China; Agriculture -- Environmental aspects -- China; Environmental policy -- China; Electronic books